Digitization of the entire traffic system and mitigation of the ongoing traffic crisis across cities of developing nations - Yasar, Mohammad Samin; Rashid, Md. Tahmid (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.